What can we learn from Severity Index on Flight Data Monitoring? Investigating the impacts of COVID-19 disrupting pilots' proficiency - Li, Wen-Chin; Nichanian, Arthur; Braithwaite, Graham; Lin, John (Cranfield University, 2023)
FDM data containing 4,761 FDM exceedance events retrieved from 123,140 flights on both Airbus and Boeing aircraft, operated in an international airline was collected from June 2019 to May 2021 for 24 months and was classified under three eight-month stages. The severity index on FDM was analyzed by event category, aircraft type, and flight phase.
Keywords: Flight Data Monitoring; 'risk assessment methods'